Analysis of English Needs for Students of Faculty of Ushuluddin and Adab UIN Sultan Maulana Hasanuddin Banten - Rani Dewi Yulyani (Edumaspul: Jurnal Pendidikan, 2023)
The research aims to analyze students' needs when participating in English language learning. The object of research was carried out on 96 students of the Faculty of Ushuluddin and Adab UIN Sultan Maulana Hasanuddin Banten with data analysis techniques using research methods used quantitative methods with survey methods of descriptive statistical data analysis. The results showed that 53 students (55.2%) were enthusiastic and happy to learn English. Then from the analysis of English learning needs that are expected there are 75.8% stating that speaking English is the most needed ability. Of the four aspects studied, students consider that listening, writing and reading skills are still needed only for academic purposes and do not feel these three aspects are necessary and support their professional careers.